PENGARUH EDUKASI INVESTASI DAN KEMAMPUAN FINANSIAL TERHADAP JUMLAH INVESTOR DI GALERI INVESTASI BEI FEB UNISMA (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis UNISMA) - Yusrotul Widad; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
In academic circles, investment is something that is not commonplace to do, even almost a few students who do not know about the flow of investing. Only a few percent university students who already know and have experience in the investment world. Especially for students of the Faculty of Economics and Business, who in fact are students who should be familiar with this. This study aims to determine the effect of investment education and financial ability on the number of investors in the Indonesian Stock Exchange Investment Gallery, Faculty of Economics and Business, Islamic University of Malang. The target of this research is students of the Faculty of Economics and Business, Islamic University of Malang. Data was collected by using a questionnaire distributed using google form. The sample in this study was 175 students. The results showed that investment education and financial ability had an effect on the number of investors in the Faculty of Economics and Business, Islamic University of Malang. Keywords: Investment Education, Financial Ability, Number of Investors.